Faktor Resiko Penularan Campak pada Anak - Eunice Kristia Sipayung; Febrina Sirait; Sri Endang Astuti Hutauruk; Pomarida Simbolon (Yayasan Literasi Sains Indonesia, 2025)
Measles is a disease that can caused by the Paramyxovirus virus. The spread of measles is very simple, namely through the droplets (saliva) of someone with measles infection that spreads in the air. measles infection that spreads in the air. This research method uses a literature review by conducting searches derived from several databases and national journals such as Garuda, Google Scholar. From literature reviewed based on research on factors associated with measles incidence. factors associated with the incidence of measles. The purpose of this study was to determine the epidemiologic picture of measles cases in children in Indonesia. Results of multivariate analysis analysis showed that the presence of household contact with measles patients contributed the highest the highest positive contribution to the incidence of measles. Spatial results showed Spatial results showed that most of the houses with measles patients were close to each other. It was found that the risk factors for measles incidence were mother's occupation, breastfeeding history, immunization status, contact history, family income, and occupancy density. The need for counseling for mothers in the care of children with measles, so as to reduce measles transmission through direct contact with their friends. direct contact with their friends. Further research should be conducted to other risk factors associated with the incidence of measles, especially for vaccine storage and cold chain factors with better methods.